A fNIRS study : effects of parenting stress on mother-child dyadic brain synchrony - Leck, Wan Qing (2019)
Parenting stress has been found to have negative impacts on children’s social development, internalizing and externalizing behaviours, health, academics and parent-child relationships. Research has shown that quality of the parent-child synchrony in early childhood has a long-lasting impact on children’s later social abilities. Given that parenting stress has been linked to poor developmental outcomes, this study was interested in examining mother-child synchrony as a possible mechanism to understand how parenting stress can impact children’s development. As such, this study investigated the effects that perceived parenting stress reported by mothers had on mother-child dyadic synchrony in the prefrontal cortex (PFC) which has been associated to Theory of Mind (ToM) and regulatory processes. Functional Near-Infrared Spectroscopy (fNIRS) was employed to simultaneously record neural activations in 37 mother-child dyads using the hyper-scanning technique during the screening of 3 short animation videos. Dynamic Time Warping (DTW) algorithm was used to generate a synchrony index. Our findings supported our hypothesis partially such that greater reported parenting stress predicted lesser synchrony in the mother-child dyad in the medial left PFC. Findings of this study provided fundamental materials critical for future studies in terms of examining parenting stress and its potential effects on mother-child relationship and co-regulation. Therapies attempting to help mothers improve their relationship with their children may potentially consider employing measures of parenting stress and mother-child synchrony as a target for therapeutic intervention. Lastly, results of this study also empower mothers to take proactive steps to ensure their own psychological well-being.